PERAN LAYANAN BIMBINGAN KONSELING DALAM MENGATASI MASALAH MOTIVASI ‎BELAJAR PESERTA DIDIK DI SEKOLAH MENENGAH - Sukatin; Anggun Janisah; Natasya Yunita Sari (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
This study aims to analyze the role of guidance and counseling services ‎in addressing students’ learning motivation problems in secondary schools. Low learning motivation is one of the factors that ‎significantly affects academic achievement and students’ personal ‎development. This research employed a descriptive qualitative approach, ‎with data collected through interviews, observations, and documentation. ‎The research subjects consisted of guidance and counseling teachers and ‎students who experienced a decline in learning motivation. The findings ‎indicate that guidance and counseling services, particularly individual ‎counseling and group counseling, play an important role in helping ‎students understand their learning problems, increase self-awareness, ‎and foster intrinsic motivation. Well-planned and continuous ‎implementation of guidance and counseling services has proven effective ‎in encouraging positive changes in students’ learning attitudes. Therefore, ‎strengthening the role of guidance and counseling teachers is essential to ‎enhance students’ learning motivation in secondary schools‎.